Portrait photograph of an unidentified child, likely female (Natick, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Henry Barrett (photographer):::Photographer:::::::::::: (Natick, MA; Henry Barrett; United States, 2023)
Portrait photograph of an unidentified child, likely female (undated) by Henry Barrett, Natick, MA, from the personal collection of Alexander Wheelock Thayer.